(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article presents the main concepts of artificial intelligence programs, as well as analyzes the prospects for the development of artificial intelligence, the main directions in the study of artificial intelligence. The first is to bring artificial intelligence systems closer to the principles of human thinking. The second is to create artificial intelligence, which is the integration of already created artificial intelligence systems into a single system capable of solving the problems of mankind.